Edição didática: práticas para a edição e produção de materiais didáticos impressos na Educação a Distância (SEDIS/UFRN) - Gonçalves, Camila Maria Gomes (2021)
This research studies book in the academic context of Distance Education in the Universidade Federal do Rio Grande do Norte, focusing on practices to edition and production. Diverse literature references – Peters (2003, 2009), Preti (2010), Moran (2002), Aretio (2002), Moore and Kearsley (2007), Filatro (2004, 2015) – pointed to the necessity of didactic material to mediate teaching-learning process in the Distance Education and, therefore, to be dialogic and collaborative to promote interaction among subjects involved in this process. This research has as base Paulo Freire’s (1979, 1980, 1982, 1987, 2001, 2004, 2009) dialogic conception, that is support to the structuration of politic-pedagogic projects of Distance Education courses from the Secretaria de Educação a Distância of the Universidade Federal do Rio Grande do Norte, locus to the development of this research. This study investigates editing practices in the production of press didactic material to the Distance Education, detaching the roles of structure and language revisor and content teacher, subjects directly responsible for the editing process, analyzing how is the dialog between these subjects, based on first versions of press materials produced in the Secretaria de Educação a Distância. It develops the concept of didactic editing as a group of functions and strategies to mediate the production of materials and the learning process, and the relationship among different subjects (teacher and students). Data are taken from first versions of didactic materials press produced by this institution, from 2014 to 2018, in a total of 20 disciplines, related to the Pedagogy, Language/Literature, Physical Education and Chemical courses, with almost 600 versions. This is a qualitative study, with exploratory aiming and methodological procedures to the literature review, based on this, it was possible to identify that working with first versions of materials produced by the content teacher is important to verify the effectiveness of revision sequence and how is its influence to the final product. Based on data analysis, it shows the didactic edition can be as a process by which the didactic material goes through until reaching its final product. It is responsible for three important functions related to the production process: orientation and communication among staff and subjects involved; compliance with the structure and to the normative characteristics required by the didactic material; didactic-pedagogical orientations to the writing. Those guides consider a group of strategies from didactic editing called practices of edition and production of didactic materials. Results aim to guide revisor trainee, the production of didactic materials to the Distance Education and the politics to this staff that consider the function of didactic materials and its importance to the distance learning.